Experimental study on water-heat-salt migration and deformation characteristics of subgrade filler during freeze-thaw cycles in Northwestern China - Hang Mu; Wenhui Zhao; Ruiqi Wang; Ke Zhang (PLoS ONE, 2025)
The seasonal freeze-thaw action of saline soils in Northwestern China deteriorates embankment material properties, thereby adversely affecting train ride comfort and increasing railway maintenance expenditures. To explore the mechanism of sulfate erosion on subgrade fillers, soil column freeze-thaw cycling tests were conducted with the background of the arching disease in the transition sections of ballastless railway culverts in Northwestern China. The water-temperature-salt migration and deformation characteristics of subgrade filler during freeze-thaw cycles are investigated. The results show that the magnitudes of temperature variations decrease upon increasing the distance from the top. Additionally, under alternating hot and cold cycles, a temperature lag occures at the lower sensors. For the multi-layer soil column, the water content increases with the number of freeze-thaw cycles. The salt content in the multi-layer soil column gradually migrates upward upon increasing the number of freeze-thaw cycles, and the overall salt content continuously increases, reaching the top of the column by the 5 th cycle. During both single-layer and multi-layer freeze-thaw cycles, the accumulated residual deformation increases with the number of cycles. Component analysis and microstructural examinations reveal the formation of ettringite and gypsum within the samples, which are related to water-heat-salt migration.